2010
DOI: 10.1680/muen.2010.163.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Survey on passenger loading in the Hong Kong airport terminal

Abstract: Emergency evacuation is the main concern in crowded airport terminals. Data on occupant loading are important for designing means of escape. However, very few field survey data on crowded terminals are available in the literature. There are queries concerning whether the data specified in the prescriptive codes are realistic in designing safety systems in modern terminals. More questions have been raised for those terminals using data, such as maximum floor area allowances per occupant, from the prescriptive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Based on the field survey conducted in 2004 during the peak period for the arrival hall [4], it is found that the actual occupant loading in the arrival hall is close to the MoE code suggested figures [5]. As the difference in the floor space factor between the field measurement and MoE code is small, it is acceptable that the designed occupant loading is based on the floor space factor, i.e.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Based on the field survey conducted in 2004 during the peak period for the arrival hall [4], it is found that the actual occupant loading in the arrival hall is close to the MoE code suggested figures [5]. As the difference in the floor space factor between the field measurement and MoE code is small, it is acceptable that the designed occupant loading is based on the floor space factor, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…The geometry of the floor plan was simplified in order to be incorporated into both models for carrying out the simulation. A field survey was conducted [4] in the airport terminal. High occupant loading was observed in some areas such as the retail areas and the arrival hall.…”
Section: Evacuation Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…The fifth paper, 'Survey of passenger loading in the Hong Kong airport terminal' (Chow and Ng, 2010), is concerned with…”
mentioning
confidence: 99%